2009
DOI: 10.1021/bi900123j
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation and Preliminary Assessment of Hydrolase Activity of PqsE, thePseudomonasQuinolone Signal (PQS) Response Protein

Abstract: In bacteria, the transcription of virulence genes is usually controlled by a cell density-dependent process known as "quorum sensing" (QS). QS relies on small diffusible signaling molecules that cross the bacterial cell wall and activate target transcription factors after a threshold concentration has been reached. Besides two hierarchical QS circuits based on N-acylhomoserine lactones, the human opportunistic pathogen Pseudomonas aeruginosa integrates a signaling system that depends on 2-heptyl-3-hydroxy-4-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 59 publications
2
101
0
1
Order By: Relevance
“…aeruginosa transcriptome is unlikely to be direct, since this protein does not possess a DNA-binding domain [37]. Moreover, PqsE activity is not exclusively a consequence of its thioesterase activity since pqsE expression is sufficient to restore pyocyanin in an AQ-deficient ( pqsA mutant) background [6,11].…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa transcriptome is unlikely to be direct, since this protein does not possess a DNA-binding domain [37]. Moreover, PqsE activity is not exclusively a consequence of its thioesterase activity since pqsE expression is sufficient to restore pyocyanin in an AQ-deficient ( pqsA mutant) background [6,11].…”
Section: Resultsmentioning
confidence: 99%
“…pqsE encodes a putative metallo-b-hydrolase of unknown function (Yu et al 2009) that appears to be ''caught'' in the positive feedback loop controlling HHQ production: it is induced as a result of this mechanism but is not required for HHQ synthesis. Nevertheless, PqsE is required for phenazine production in P. aeruginosa PAO1 and PA14 (Gallagher et al 2002;Recinos et al 2012).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Constitutive expression of PqsE in a pqsA mutant background is sufficient to promote phenazine production , suggesting that, in the context of phz operon expression, the positive feedback loop that promotes HHQ production serves the The mechanism whereby PqsE promotes phz operon expression remains completely undefined, as PqsE itself does not contain a DNA binding domain. PqsE may be involved in the transformation of an unknown signal (Yu et al 2009). We hypothesize that this signal controls the activity of an unidentified regulator of phz gene expression.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Transcription of pqsABCDE leads to the expression of the fifth gene in the operon, PqsE. The precise function of PqsE is not understood; however, structural analysis indicated that PqsE is related to the metallo-␤-lactamase superfamily and is not required for HAQ biosynthesis but independently regulates genes that are under PQS control (16)(17)(18). PqsE is required for swarming motility and biofilm formation and can activate virulence in the absence of a functional pqs system (19).…”
mentioning
confidence: 99%